PENGARUH LINGKUNGAN FISIK DAN KESENANGAN KONSUMEN BERBELANJA TERHADAP PEMBELIAN TIDAK DIRENCANAKAN - Hidayatul Mustafidd; Mira Maulani Utami (Tirtayasa Ekonomika, 2016)
The purpose of this paper that determine whether the service scape and hedonic shopping value can influence impulse buying. The method used to analyze using descriptive methods. Data collection techniques using a questionnaire with Likert scale. Utilizing purposive sampling technique, with the fololwing criteria, the people who have ever bought in K Store at least once, then 100 samples meet criteria for sample. Soft ware analysis techniques SPSS V 20 are used in this research. The final results indicate that , there are positive effects of services cape and hedonic shopping value on impulse buying .This study has important managerial implications, K-Store Cilegon is necessary to maintain and improve service such as providing an entertainment place. And it is necessary to maintain and improve comfort in K-Store, such as, cleanleness. In addition, researchers suggest that K-Store is be able to pay attention to the layout plan especially in the fruits and fresh produce area , so the atmosphere does not interfere convenience of shopping Keyword : Servicescape, Hedonic Shopping Value and Impulse Buying.